2018
DOI: 10.1007/s00702-018-1908-y
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase-A, serotonin and norepinephrine: synergistic players in cardiac physiology and pathology

Abstract: The mitochondrial enzyme monoamine oxidase A (MAO-A) is widely distributed in neuronal, myocyte and non-myocyte cardiac compartments. After the demonstrations that both cardiac neuronal and extraneuronal MAO-A contribute to the degradation of norepinephrine and serotonin, several studies attempted to determine the impact of MAO-A activity in the control of local concentration of the two biogenic amines and in their receptor-mediated effects. From the 2000s, an additional mechanism of action of MAO-A has been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…Studies have shown that increased serotonin uptake and oxidative stress could be the cause of platelet activation. Increased serotonin metabolism and subsequent MAO activity induce oxidative stress, and consequently, oxidative stress may activate platelet activation (Bianchi, Pimentel, Murphy, Colucci, & Parini, ; Mialet‐Perez, Santin, & Parini, ; Sugiura et al, ). Our result showed a significant elevation of ROS in patient with PD and reduction in TAC, so it can affect the RBC membrane and causes significant alterations of RDW and MCHC (Mehrpour et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that increased serotonin uptake and oxidative stress could be the cause of platelet activation. Increased serotonin metabolism and subsequent MAO activity induce oxidative stress, and consequently, oxidative stress may activate platelet activation (Bianchi, Pimentel, Murphy, Colucci, & Parini, ; Mialet‐Perez, Santin, & Parini, ; Sugiura et al, ). Our result showed a significant elevation of ROS in patient with PD and reduction in TAC, so it can affect the RBC membrane and causes significant alterations of RDW and MCHC (Mehrpour et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since high levels of ROS are generated during the development of ischemia/reperfusion injury as well as upon the oxidation of catecholamines by both enzymatic and non-enzymatic mechanism, it has been argued that ventricular arrhythmias are induced by oxidative stress in the myocardium [ 5 , 6 , 14 , 44 , 45 , 46 , 47 , 48 ]. This concept is consistent with observations [ 15 ] that treatment of animals with well-known antioxidants such as vitamin E and N -acetyl-cysteine prevented the epinephrine-induced different types of arrhythmias as well as increased the levels of plasma malondialdehyde, an index of oxidative stress ( Table 3 ).…”
Section: Oxidative Stress As a Factor For Increasing The Risk Of Amentioning
confidence: 99%
“…Thus, the beneficial effects of angiotensin converting enzyme inhibitors as well as angiotensin II receptor blockers in attenuating ventricular arrhythmias in ischemic heart disease appears to be due to reduction in the degree of oxidative stress. Likewise, the prevention of ventricular arrhythmias due to coronary artery occlusion by a 5-hydroxytryptamine (5-HT) receptor inhibitor, sarpogrelate [ 17 , 75 ], may also be attributed to its effect on oxidative stress because the circulating level of serotonin (5-HT) was increased in myocardial infarction [ 76 ] and serotonin has been shown to generate oxyradicals upon oxidation due to monoamine oxidase [ 48 ].…”
Section: Oxidative Stress As a Factor For Increasing The Risk Of Amentioning
confidence: 99%
“…2 A depletion of serotonin in the CNS is responsible for disorders such as obsessive–compulsive disorders, depression, and anxiety, 3 while its role in mediating inflammation and immunity responses 4 as well as its relevance for cardiac physiology and pathology has also been proposed. 5 Increasing serotonin levels is an important strategy in the pharmacological treatment of depression, and typically, the levels are increased by inhibiting the serotonin transporter or by inhibiting monoamine oxidase A (MAO A), an enzyme that breaks down serotonin. 6 MAOs are flavoenzymes that catalyze the oxidative deamination of biogenic amines, producing aldehyde and hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%